2009
DOI: 10.1007/s00146-009-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Game feature and expertise effects on experienced richness, control and engagement in game play

Abstract: The extent to which game play is experienced as engaging is an important criterion for the playability of video games. This study investigates how video games can be designed towards increased levels of experienced engagement over time. For this purpose, two experiments were conducted in which a total of 35 participants repeatedly played a video game. Results indicate that experienced engagement is based on the extent to which the game provides rich experiences as well as by the extent to which the game provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Game-control distribution did not appear to affect the levels of experienced richness. Earlier studies showed that experienced richness is affected by the number of game functions (Rozendaal et al 2007a(Rozendaal et al , 2009a, and-based on the current results-not by the extent to which they are distributed among the players.…”
Section: Game-control Distribution Effectssupporting
confidence: 47%
See 2 more Smart Citations
“…Game-control distribution did not appear to affect the levels of experienced richness. Earlier studies showed that experienced richness is affected by the number of game functions (Rozendaal et al 2007a(Rozendaal et al , 2009a, and-based on the current results-not by the extent to which they are distributed among the players.…”
Section: Game-control Distribution Effectssupporting
confidence: 47%
“…An engagement framework has been developed to explicate the experience of engagement and the factors influencing it in order to support interactive system design (Rozendaal et al 2009a(Rozendaal et al , 2009b.…”
Section: Experienced Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryan (as cited by Brown, 2008) considered complex branching narrative structures in RPGs to be approaching the "ultimate goal of art" in virtual reality: a seamless merging of narrative and simulation that preserves both a coherent narrative structure and the ability for the user to influence the progression of the story. Richness experienced during game play relates to perceived complexities and is associated with an increase of the degrees of freedom to which a game can be manipulated (Rozendaal, Keyson, de Ridder, & Craig, 2009). Rozendaal et al (2009) found that experienced richness promotes engagement due to the excitement experienced when perceiving a game's potential for developing human faculties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Richness experienced during game play relates to perceived complexities and is associated with an increase of the degrees of freedom to which a game can be manipulated (Rozendaal, Keyson, de Ridder, & Craig, 2009). Rozendaal et al (2009) found that experienced richness promotes engagement due to the excitement experienced when perceiving a game's potential for developing human faculties.…”
Section: Literature Reviewmentioning
confidence: 99%